2019
DOI: 10.3389/fcimb.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Global Phosphoproteomics Reveals Novel Molecular Differences Between Toxoplasma gondii Strains of Different Genotypes

Abstract: To gain insights into differences in the virulence among T. gondii strains at the post-translational level, we conducted a quantitative analysis of the phosphoproteome profile of T. gondii strains belonging to three different genotypes. Phosphopeptides from three strains, type I (RH strain), type II (PRU strain) and ToxoDB#9 (PYS strain), were enriched by titanium dioxide (TiO2) affinity chromatography and quantified using iTRAQ technology. A total of 1,441 phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…KEGG pathway analysis showed that the identified phosphoproteins were annotated into pathways with direct relevance to toxoplasmosis and metabolism, such as "Glycerophospholipid metabolism" and "Metabolic pathways" (Table S3, Figure S1), which is consistent with the reported phosphoproteins function in the phosphoproteomic analysis of different T. gondii strains (Wang et al, 2019). This result suggests that phosphoprotein-mediated pathway regarding toxoplasmosis and metabolism may be critical for the pathogenesis of T. gondii.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…KEGG pathway analysis showed that the identified phosphoproteins were annotated into pathways with direct relevance to toxoplasmosis and metabolism, such as "Glycerophospholipid metabolism" and "Metabolic pathways" (Table S3, Figure S1), which is consistent with the reported phosphoproteins function in the phosphoproteomic analysis of different T. gondii strains (Wang et al, 2019). This result suggests that phosphoprotein-mediated pathway regarding toxoplasmosis and metabolism may be critical for the pathogenesis of T. gondii.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Wang et al analyzed the phosphoproteome of three different strains of T. gondii tachyzoites (RH strain, PRU stain, and PYS strain), and identified several hundreds of phosphoproteins. This phosphoproteomic analysis is therefore beneficial for explaining the contribution of phosphorylation in regulating the virulence heterogeneity of the three parasite strains ( Wang et al, 2019 ). In our study, however, only 38 phosphoproteins were identified, which were much less than the reported number of phosphoproteins in T. gondii tachyzoites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, TgWNGI, a parasite specific kinase, has been shown to phosphorylate and regulate the association of GRAs such as GRA17 with the membrane (Beraki et al, 2019). However, GRA60 is not reported to be phosphorylated in any of the available phosphoproteome analyses (Z. X. Wang, Zhou, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of tissue culture and mouse inoculation methods for the demonstration of T. gondii organisms were found to be equal [24]. In addition, many studies prepared tachyzoites using mice inoculation [15,25,26,27,28,29]. The purpose of our research was to investigate acetylomic signatures of different genotypes of Toxoplasma gondii purified in vivo .…”
Section: Methodsmentioning
confidence: 99%